2018
DOI: 10.1038/s41598-018-21414-w
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Differentiation of Crop Growth as One of the Drivers of Intercropping Yield Advantage

Abstract: Intercropping studies usually focus on yield advantage and interspecific interactions but few quantify temporal niche differentiation and its relationship with intercropping yield advantage. A field experiment conducted in northwest China in 2013 and 2014 examined four intercropping systems (oilseed rape/maize, oilseed rape/soybean, potato/maize, and soybean/potato) and the corresponding monocultures. Total dry matter data collected every 20 d after maize emergence were fitted to logistic models to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 50 publications
1
30
0
1
Order By: Relevance
“…Intercropping has been well known as one kind of the sustainable agricultural cropping patterns around the world [17][18][19]. Many studies have demonstrated that intercropping not only has obvious advantages on the increase of crop productivity [20][21][22] and efficient exploration of agricultural resources [23,24] when compared with crop monoculture, but simultaneously it can also suppress the soil-borne diseases [17]. Recent research indicated that intercropping reduced the occurrence of Phytophthora blight of pepper in maize/pepper intercropping [25], suppressed the incidence of Fusarium wilt of watermelon in rice/watermelon intercropping [26] and wheat/maize intercropping [15,27], and soybean red crown rot caused by Cylindrocladium parasiticum in maize/soybean intercropping [14].…”
Section: Introductionmentioning
confidence: 99%
“…Intercropping has been well known as one kind of the sustainable agricultural cropping patterns around the world [17][18][19]. Many studies have demonstrated that intercropping not only has obvious advantages on the increase of crop productivity [20][21][22] and efficient exploration of agricultural resources [23,24] when compared with crop monoculture, but simultaneously it can also suppress the soil-borne diseases [17]. Recent research indicated that intercropping reduced the occurrence of Phytophthora blight of pepper in maize/pepper intercropping [25], suppressed the incidence of Fusarium wilt of watermelon in rice/watermelon intercropping [26] and wheat/maize intercropping [15,27], and soybean red crown rot caused by Cylindrocladium parasiticum in maize/soybean intercropping [14].…”
Section: Introductionmentioning
confidence: 99%
“…There are many intercropping models, such as chickpea/maize [3], maize/lablab [4], rubber/plantain [5], even marine finfish in shrimp ponds [6]. Intercropping showed many advantages, like higher yield [7,8], higher light interception and utilization rate [9], phytoremediation of heavy metal contaminated soils [10], enhancing iron nutrition [11] and phosphorus availability [12], etc.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of limited cultivated land resources in China, intercropping systems were important measures to improve land utilization efficiency [1][2][3][4]. Among intercropping systems, the maize-soybean intercropping system in southwest China has achieved the purpose of improving the yield of soybean and maize [5].…”
Section: Introductionmentioning
confidence: 99%